Stresses as First-Line Tools for Enhancing Lipid and Carotenoid Production in Microalgae - Shi, Tian-Qiong; Wang, Ling-Ru; Zhang, Zi-Xu; Sun, Xiao-Man; Huang, He (Frontiers in Bioengineering and Biotechnology, 2020)
Microalgae can produce high-value-added products such as lipids and carotenoids using light or sugars, and their biosynthesis mechanism can be trigged by various stress conditions. Under nutrient deprivation or environmental stresses, microalgal cells accumulate lipids as an energy-rich carbon storage battery, and generates additional amounts of carotenoids to alleviate oxidative damage induced by stress conditions. Although stressful conditions are unfavorable to biomass accumulation, and can induce oxidative damage. Given its effectiveness and economy, stresses-based strategy are widely used in this field yet. For overproduction of different target products, it is required and meaningful to deeply understand the effects and mechanisms of various stress conditions, which can give guidance on choose of the appropriate stress conditions. Moreover, the underlying molecular mechanisms under stress conditions can be clarified by omics technologies, which exhibits enormous potential in guiding rational genetic engineering for improving lipid and carotenoids biosynthesis.